Does the technique of interventional closure of perimembranous ventricular septal defect reduce the incidence of heart block? - Bentham, James R.; Gujral, Arjun; Adwani, Satish; Archer, Nick; Wilson, Neil (Cardiology in the young, 2011)
To describe the difficulties and differing techniques in the transcatheter placement of amplatz ventricular septal defect devices to close perimembranous ventricular septal defects and place these in the context of the expanding literature on ventricular septal defect catheter closure. Surgery remains the established first-line therapy for closure of haemodynamically significant perimembranous ventricular septal defects. Transcatheter techniques appeared to promise a possible alternative, obviating the need for cardiac surgery. However, significant technical and anatomical constraints coupled with ongoing reports of a high incidence of heart block have prevented these hopes from being realised to any significant extent. It is likely that there are important methodological reasons for the high complication rates observed. The potential advantages of transcatheter perimembranous ventricular septal defect closure over surgery warrant further exploration of differing transcatheter techniques. Between August, 2004 and November, 2009, 21 patients had a perimembranous ventricular septal defect closed with transcatheter techniques. Of these, 14 were closed with a muscular amplatz ventricular septal defect device. The median age and weight at device placement were 8 years, ranging from 2 to 19 years, and 18.6 kilograms, ranging from 10 to 21 kilograms, respectively. There were 25 procedures performed on 23 patients using 21 amplatz ventricular septal defect devices. Median defect size on angiography was 7.8 millimetres, ranging from 4 to 14.3 millimetres, with a median device size of 8 millimetres, ranging from 4 to 18 millimetres, and a defect/device ratio of 1.1, with a range from 0.85 to 1.33. Median procedure time was 100 minutes, with a range from 38 to 235 minutes. Adverse events included device embolisation following haemolysis in one, and new aortic incompetence in another, but there were no cases of heart block. Median follow-up was 41.7 months, with a range from 2 to 71 months. Evaluating transcatheter closure of perimembranous ventricular septal defect using amplatz ventricular septal defect devices remains important, if a technically feasible method with low and acceptable complication rates is to be identified. Incidence of heart block may be minimised by avoiding oversized devices, using muscular devices, and accepting defeat if an appropriately selected device pulls through. Given the current transcatheter technologies, the closure of perimembranous ventricular septal defects should generally be performed in children when they weigh at least 10 kilograms.